Colour analysis in sausages stuffed in modified casings with different storage days using hyperspectral imaging – A feasibility study. (May 2020) - Feng, Chao-Hui; Makino, Yoshio
Abstract: Colour evolution for sausage stuffed in casings modified by different concentrations of surfactant solution and slush salt with lactic acid was for the first time investigated during 68 days with 4 °C storage using a hyperspectral imaging system in the range of 380–1000 nm. Pre-treatments (normalization, standard normal variate (SNV), multiplicative scatter correction (MSC), first and second derivative) were conducted and performance after the pre-treatments was improved. No interactive effects between casing treatments and storage days were observed in accordance with two-way ANOVA. Partial least squares regression (PLSR) was developed from spectra with reflectance and absorbance modes and important wavelengths were selected with regard to each colour parameters. When predicted redness (a*), PLSR model derived from absorbance pre-treated by MSC for modified casing with treatment 1 showed the prediction coefficient of determination (Rp 2 ) up to 0.78 while 0.61 for control casing using reflectance. This study innovatively showed a great potential in a cylinder shape sausage for real-time inspection and is competent to quantify and visualise the colour dynamic change of the sausages stuffed in modified casings. Highlights: A cylinder-shape sausage was for the first time applied to hyperspectral imaging. Redness evolution of sausage with modified casing was visualised by distribution map. PLSR was developed from spectra with reflectance and absorbance modes. Placing sausage vertically can solve the shadow problem during scanning. Lightness of sausages in modified casing tended to be more stable than control sample.